Feasibility of Applying Pattern Search Optimization to Optical Couplers - Ozkan-Bakbak, Pinar; Unverdi, N. Ozlem (IEEE, 2018)
There are many application areas of optical directional couplers, which are among the elements of optical ciruits, such as power distribution, optical switching, wavelength filtering, and polarization selection. In this study, applicability of Pattern Search Optimization (PSO), which is a simple and fast optimization method, to optical directional couplers, which have complex modal analysis results, is shown. It is observed that the results of Pattern Search Optimization (PSO), which is preferred because of its ease of implementation and fast convergence ability, are in coherence with analytical findings. It is ascertained that PSO and other evolutionary algorithms, because of their sophisticated formulations, are suitable for the optimization of many complex optical circuit elements.
Keywords: Communication technologies; optical communications; optical coupler; pattern search optimization; Engineering; Telecommunications